The Behavior of Little Pied Cormorant (Phalacrocorax melanoleucos) in Serangan Island, Bali - Vitrayanthi, Putu Ayu Wiwin; Watiniasih, Ni Luh; Ginantra, I Ketut (Metamorfosa: Journal of Biological Sciences, 2019)
Serangan island is part of Ngurah Rai Forest Park. Fifty five species of birds, belong to 30 families have been found in Serangan island. Based on earlier information that Phalacrocorax melanoleucos was commonly shown in lagoon and mangrove. This study aimed to investigate the habitat condition and  the behavior of P. melanoleucos in Serangan Island. The study has been conducted from November 2016 to May 2017, in lagoon area of Serangan Island in two observation points of 8º44.647? S  115º13.332? E and 8º44.769? S 115º345? E. Scan sampling technique was applied to collect the data of the bird behavior and the data of species of plant being used by P. Melanoleucos was collected by tracking methods. P. melanoleucos was commonly found foraging in the morning (45 % ± 0.15 %). Similar pattern of behavior was observed during the day and in the afternoon, but the amount of time spent for perching during the day and afternoon were slighly lower, 42 % ± 0.02 % and 41 % ± 0.02 % respectively. Agonistic  behaviour was rarely observed during the study (5 % ± 0.06 %). Casuarina equisetifolia and Soneratia alba plants were commonly used by birds for perching. Key words : Serangan island, habitat, Scan sampling, Phalacrocorac melanoleucos, perching,